Pengaruh Pemberian Aromaterapi Pandan Wangi (Pandanus amaryllifolius) dan Lemon (Citrus limon L) dalam Menurunkan Tekanan Darah: The Effect of Aromatherapy Pandan Wangi (Pandanus amaryllifolius) and Lemon (Citrus limon L) in Lowering Blood Pressure - Jihan Al-Mira; Adam M. Ramadhan; Fika Aryati (Proceeding of Mulawarman Pharmaceuticals Conferences, 2021)
Fragrant pandan and lemon contain linalool compounds as much as 6% in fragrant pandan and as much as 20-50% are found in lemons, linalool compounds are very useful for stabilizing nerves so that they can have a calming effect. This study aims to determine the characteristics, description of the respondent's blood pressure before and after being given aromatherapy, and the effect of giving pandanus and lemon aromatherapy on the blood pressure of hypertension respondents who live in the Sempaja Timur Village. The research method used is a quasi-experimental method with a one group pretest and posttest design with a total of 20 respondents. The research procedure uses initial and final measurements. The results showed that the characteristics of the highest hypertension respondents were female as many as 15 respondents( 75%), 10 respondents aged 60 years (50%), work as a housewife as many as 13 respondents (65%), and the antihypertensive drug consumed was amlodipine as much as 20 respondents ( 100%). The results of this study found that there was an effect of giving aromatherapy pandanus and lemon on systolic blood pressure before being given aromatherapy with an average of 162.6 mmHg and after being given aromatherapy an average of 156.4 mmHg while diastolic blood pressure before giving aromatherapy was on average by 99.6 mmHg and after being given aromatherapy an average of 94.4 mmHg. The results of the descriptive study of giving fragrant pandan and lemon aromatherapy are in line with the results of statistical analysis using the Wilcoxon test method and the paired sample t-test with a p value (0,000) <0.05. hypertension significantly.